2016
DOI: 10.1016/j.jamcollsurg.2016.08.568
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Score Predicting Long-Term Survival after Repeat Resection for Recurrent Adrenocortical Carcinoma

Abstract: BACKGROUND Adrenocortical carcinoma (ACC) is an aggressive malignancy typically resistant to chemotherapy and radiation. Surgery, even in the setting of locally recurrent or metastatic disease, remains the only potentially curative option. However, the subset of patients who will benefit from repeat resection in this setting remains ill defined. The objective of this study was to propose a prognostic clinical score that facilitates selection of patients for repeat resection of recurrent ACC. STUDY DESIGN Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…HIPEC also proved effective in pursuing local/peritoneal control of recurrent disease, albeit this result appears less appreciable than in the SP setting. It is difficult to compare our result with those reported in literature [17][18][19][20], as patient characteristics and treatment strategies may be different as are the considered end points of the studies. However, the median l/pDFS of 12 months observed in our cohort was almost double compared to those previously reported.…”
Section: Surgery For Recurrencementioning
confidence: 81%
See 1 more Smart Citation
“…HIPEC also proved effective in pursuing local/peritoneal control of recurrent disease, albeit this result appears less appreciable than in the SP setting. It is difficult to compare our result with those reported in literature [17][18][19][20], as patient characteristics and treatment strategies may be different as are the considered end points of the studies. However, the median l/pDFS of 12 months observed in our cohort was almost double compared to those previously reported.…”
Section: Surgery For Recurrencementioning
confidence: 81%
“…Rescue surgery for early recurrence (median 7 months) was performed in 9/14 cases, all patients presented multiple nodules of recurrence, and those patients for whom a CC0 cytoreduction could not be achieved were treated. All these clinical conditions are negative prognostic factors [8,19,20], and the exclusion of possible bad performers could have positively influenced survival outcome. A second point regards the technical aspect of HIPEC.…”
Section: Surgery For Recurrencementioning
confidence: 99%
“…Dy et al also identified patients with a disease‐free interval greater than 6 months to benefit from surgical resection . Tran et al found that favorable prognosis after reoperation may be expected when at least two of the following factors are present, namely: a solitary tumor, disease‐free interval greater than 12 months and locoregional or pulmonary recurrence. Finally, Patel et al identified elevated serum IGFBP2 to be associated with improved survival after reoperation in recurrent ACC.…”
Section: Discussionmentioning
confidence: 99%
“…12 Dy et al 10 also identified patients with a disease-free interval greater than 6 months to benefit from surgical resection. 10 Tran et al 27 should be used with caution and clinicians should be aware of these weaknesses. However, none of the clinical factors that were studied was significantly associated with elevated or reduced levels of LMR.…”
Section: The Relationship Between Systemic Inflammatory Markers Andmentioning
confidence: 99%
“…Given the high rates of recurrence, salvage therapy options are important but remain currently underinvestigated. In patients with recurrent ACC, the benefits of repeat resection are contested, though, may be indicated in select patients who meet favorable criteria [8]. The utility of adjuvant mitotane or chemotherapy following resection of metastatic or recurrent disease remains unclear [8].…”
mentioning
confidence: 99%